Catalase, Glutathione Peroxidase, and Peroxiredoxin 2 in Erythrocyte Cytosol and Membrane in Hereditary Spherocytosis, Sickle Cell Disease, and β-Thalassemia - Daniela Melo; Fátima Ferreira; Maria José Teles; Graça Porto; Susana Coimbra; Susana Rocha; Alice Santos-Silva (MDPI AG, 2024)
Catalase (CAT), glutathione peroxidase (GPx), and peroxiredoxin 2 (Prx2) can counteract the deleterious effects of oxidative stress (OS). Their binding to the red blood cell (RBC) membrane has been reported in non-immune hemolytic anemias (NIHAs). Our aim was to evaluate the relationships between CAT, GPx, and Prx2, focusing on their role at the RBC membrane, in hereditary spherocytosis (HS), sickle cell disease (SCD), β-thalassemia (β-thal), and healthy individuals. The studies were performed in plasma and in the RBC cytosol and membrane, evaluating OS biomarkers and the enzymatic activities and/or the amounts of CAT, GPx, and Prx2. The binding of the enzymes to the membrane appears to be the primary protective mechanism against oxidative membrane injuries in healthy RBCs. In HS (unsplenectomized) and β-thal, translocation from the cytosol to the membrane of CAT and Prx2, respectively, was observed, probably to counteract lipid peroxidation. RBCs from splenectomized HS patients showed the highest membrane-bound hemoglobin, CAT, and GPx amounts in the membrane. SCD patients presented the lowest amount of enzyme linkage, possibly due to structural changes induced by sickle hemoglobin. The OS-induced changes and antioxidant response were different between the studied NIHAs and may contribute to the different clinical patterns in these patients.